Postprandial hypoglycaemia after Roux‐en‐Y gastric bypass and the effects of acarbose, sitagliptin, verapamil, liraglutide and pasireotide. Issue 9 (24th June 2019) - Øhrstrøm, Caroline Christfort; Worm, Dorte; Højager, Anna; Andersen, Ditte; Holst, Jens Juul; Kielgast, Urd Lynge; Hansen, Dorte Lindqvist
Abstract: Aim: To investigate the effects of acarbose, sitagliptin, verapamil, liraglutide and pasireotide on post‐bariatric hypoglycaemia (PBH) after Roux‐en‐Y gastric bypass. Materials and methods: In a randomized crossover study, 11 women who had undergone Roux‐en‐Y gastric bypass and had documented hypoglycaemia were each evaluated during a baseline period without treatment and during five treatment periods with the following interventions: acarbose 50 mg for 1 week, sitagliptin 100 mg for 1 week, verapamil 120 mg for 1 week, liraglutide 1.2 mg for 3 weeks and pasireotide 300 μg as a single dose. Treatment effects were evaluated by a mixed‐meal tolerance test (MMTT) and, for all treatment periods except pasireotide, by 6 days of continuous glucose monitoring (CGM). Results: Treatment with acarbose and treatment with pasireotide both significantly lifted nadir glucose levels (mean ± SEM 3.9 ± 0.2 and 7.9 ± 0.4 vs 3.4 ± 0.2; P  < .03) and reduced time in hypoglycaemia during the MMTTs. Acarbose reduced peak glucose levels and time in hyperglycaemia, whereas pasireotide greatly increased both variables. Acarbose and pasireotide reduced insulin and C‐peptide levels, and pasireotide also diminished glucagon‐like peptide‐1 levels. Sitagliptin lowered nadir glucose values, while verapamil and liraglutide had no effect on hypoglycaemia. During the CGM periods, the treatments had no impact on hypoglycaemia, whereas acarbose and liraglutide reduced hyperglycaemia and glycaemic variability. Conclusions: In an experimental setting, treatment with acarbose and pasireotide reduced PBH. Acarbose appears to have an overall glucose‐stabilizing effect, whereas pasireotide leads to increased and sustained hyperglycaemia.